Modified Laminoplasty After Excision of Cervical Schwannoma with Large Extravertebral Extension - Muhammad Faris; Abdul Hafid Bajamal; Zaky Bajamal; Krisna Tsaniadi Prihastomo (Neurologico Spinale Medico Chirurgico, 2018)
Tumour excision and laminoplasty are commonly performed as surgical treatment of extra vertebral extension of cervical schwannoma. It is worth knowing that the conventional technique of multilevel laminectomy may hinder younger patients in the long-term. This article reports a 30-year old man with an intradural-extramedullary tumour which extended from C4 to T1 that underwent modified laminoplasty. This modified technique is preferable in maintaining the anteroposterior diameter of spinal canal as well as reducing the displacement of guttered laminae